Metaphysics of Practical Philosophy. The Concept of Capacity in Aristotle - Makowski, Piotr (Logos Verlag, 2009)
The author presents the Aristotelian conception of capacity/potentiality (dynamis), which is part of Aristotle’s basic philosophical vocabulary. The concept of capacity is one of the most important in Aristotle’s metaphysics. Its significance can be seen in the link between metaphysics and practical wisdom (ethics, rhetoric, politics): the author analyzes this link in Aristotle on the base of the concept of capacity. Demonstrating the connection between theory and practice is based on the most important parts of Metaphysics (books delta and theta) and relates metaphysical definitions to an essential element of Aristotelian practical philosophy – the concept of virtue (aretê). In the practical works of Aristotle (three ethics and rhetoric) it is possible to find definitions of aretê which differ: in Nicomachean Ethics Aristotle defines aretê using the notion of disposition (hexis), but in Rhetoric he formulates the definition based on the concept of capacity. Distinctive analysis of this inconsistency shows the significance of capacity in The Stagirite’s philosophy.
Keywords: Aristotle; capacity; metaphysics; ethics; rhetoric; practical philosophy